Expanding Statism through Sovereign Investment? Evidence from the Domestic-Focused Indonesia Investment Authority - Cahyafitri, Raras (Jurnal Hubungan Internasional, 2025)
This study examined Indonesia’s first-ever sovereign wealth fund (SWF), known as the Indonesia Investment Authority (INA), focusing on domestic investment. While some newly established SWFs prioritize domestic markets, most of the traditional sovereign funds invest overseas. This study questions INA’s establishment considering this trend. Through qualitative analysis of secondary data, this research argues that INA’s domestic orientation, structure, and investment objective reflect a growing trend of expanding statism, whereby the government leverages the sovereign fund to shape public and private capital allocation for national projects. INA’s co-investment scheme has enabled non-state actors to maintain their capital ownership while the fund determines investment directions. Given the growing number of SWFs worldwide with varied business models, concerns have emerged that governments may utilize them as instruments of power.